Formation of the communicative competence of Russian and foreign electrical students during the socio-cultural project - Malkova, Maria Vladimirovna (Известия Саратовского университета: Новая серия. Серия Философия. Психология. Педагогика, 2023)
Introduction. The problem of the formation of communicative competence among Russian and foreign students in the classroom in a foreign language requires the introduction of an integrated approach to learning. Such an innovative form of education as a project, namely, a socio-cultural project that includes professional tests, provides an opportunity for intercultural mutual enrichment and the use of language knowledge in everyday and professional communication. Theoretical analysis of the material on this issue led to the conclusion that it is necessary to introduce professional tests in Russian and foreign languages into the practice of training future engineers. Empirical analysis. The author of the article offers an experimental experience – intercultural interaction in the system of professional trials of Russian and foreign students. Foreign students get acquainted with the basics of electrical engineering already at the stage of pre-university training, which contributes to the development of interest in their future specialty. Russian students gain experience of communication in a foreign language as part of their professional activities. Conclusion. The novelty of this form of education lies in the fact that the cooperation of Russian and foreign students is not limited to one-time joint professional practices, but is combined into a sociocultural professionally oriented project.